2008
DOI: 10.1161/hypertensionaha.107.107268
|View full text |Cite
|
Sign up to set email alerts
|

The Collecting Duct Is the Major Source of Prorenin in Diabetes

Abstract: Abstract-In addition to the juxtaglomerular apparatus, renin is also synthesized in renal tubular epithelium, including the collecting duct (CD). Angiotensin (Ang) II differentially regulates the synthesis of juxtaglomerular (inhibition) and CD (stimulation) renin. Because diabetes mellitus, a disease with high intrarenal renin-Ang system and Ang II activity, is characterized by high prorenin levels, we hypothesized that the CD is the major source of prorenin in diabetes. Renin granular content was visualized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
212
2
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(230 citation statements)
references
References 33 publications
10
212
2
5
Order By: Relevance
“…4B). Consistent with this result, plasma renin measurements (27,28) revealed that Olfr78 −/− mice fed a standard chow diet rich in plant polysaccharides have significantly lower plasma renin levels than wild-type mice fed the same diet ( Fig. 4C, P < 0.05).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…4B). Consistent with this result, plasma renin measurements (27,28) revealed that Olfr78 −/− mice fed a standard chow diet rich in plant polysaccharides have significantly lower plasma renin levels than wild-type mice fed the same diet ( Fig. 4C, P < 0.05).…”
Section: Resultssupporting
confidence: 77%
“…Propionate (P) induces quinacrine release (which is a surrogate for renin release) in wild-type but not Olfr78 −/− animals (B). PRA levels (plasma renin activity, normalized ex vivo to wild-type and determined as the slope of the time course of fluorescent product production in a kinetic assay) (27,28) are significantly reduced in Olfr78 −/− mice (C). * indicates statistical significance.…”
mentioning
confidence: 99%
“…A recent study A c c e p t e d M a n u s c r i p t 6 suggests that the source of the elevated prorenin in diabetes mellitus is the collecting duct. Unexpectedly, at this site Ang II stimulates the synthesis of prorenin (Kang et al, 2008), as opposed to its inhibiting effects in the juxtaglomerular apparatus. Furthermore, plasma prorenin in diabetic subjects plasma was found to correlate with the renovascular response to captopril (Stankovic et al, 2006).…”
Section: Proreninmentioning
confidence: 90%
“…19,[46][47][48][49][50][51][52][53][54] Interestingly, mechanisms for regulating tubular renin seem to be independent of those in the JG cell. 47,48,50,52 Proximal tubular cells express mRNA [54][55][56] and protein 53,57 for ACE and Aogen. [58][59][60][61] In vivo evidence that proximal tubular cells may synthesize Ang II has also been reported.…”
Section: Intrarenal Raasmentioning
confidence: 99%
“…The intrarenal RAAS is thought to be activated during diabetes, based on in vitro and in vivo evidence. 21,22,24,25,48,54,55,69,78 Therefore, the effect of renin inhibition in diabetic conditions is of great interest.…”
Section: Testing Aliskiren In Animal Modelsmentioning
confidence: 99%